Increase of environmental competence of teachers of professional and technical schools of the contruction profile - Kulalaieva, Natalia V. (Journal of the Belarusian State University. Ecology, 2018)
The article outlines the main environmental issues of our time that have affected Ukraine. The solution of these issues is possible only due to the wide implementation of education for sustainable development. The author substantiates the necessity of increasing the environmental competence of Ukrainian teachers of professional and technical schools of the construction profile for the implementation of environmental knowledge in the training of future builders by introducing distance courses developed with the participation of the author. The analysis of the content of normative international and Ukrainian documents on the introduction of the environmental component into the professional education of Ukraine is given. It is proved that future builders need to form a holistic view of the consequences of the impending crisis caused by demographic, energy, resource, economic, social and other processes. There are given the examples of initiatives of educational institutions of different degrees of accreditation implementing the strategy of environmental education in Ukraine. The structure, as well as the goals of the modules developed by the author, of distance courses for increasing the environmental competence of teachers of professional and technical education of Ukraine are considered. The conceptual bases of the indicated distance courses are grounded: methodological approaches, didactic principles of training, criteria for selection and structuring of the content of the educational material.
Keywords: education for sustainable development; environmental competence; professional-technical schools of the construction profile; implementation of environmental knowledge; distance Learning courses; professional training of future builders